On the Possibility of an Early Evolutionary Origin for the Spliced Leader Trans-Splicing - Krchňáková, Zuzana; Krajčovič, Juraj; Vesteg, Matej (Journal of molecular evolution, 2017)
Trans-splicing is a process by which 5'- and 3'-ends of two pre-RNA molecules transcribed from different sites of the genome can be joined together to form a single RNA molecule. The spliced leader (SL) trans-splicing is mediated by the spliceosome and it allows the replacement of 5'-end of pre-mRNA by 5'(SL)-end of SL-RNA. This form of splicing has been observed in many phylogenetically unrelated eukaryotes. Either the SL trans-splicing (SLTS) originated in the last eukaryotic common ancestor (LECA) (or even earlier) and it was lost in most eukaryotic lineages, or this mechanism of RNA processing evolved several times independently in various unrelated eukaryotic taxa. The bioinformatic comparisons of SL-RNAs from various eukaryotic taxonomic groups have revealed the similarities of secondary structures of most SL-RNAs and a relative conservation of their splice sites (SSs) and Sm-binding sites (SmBSs). We propose that such structural and functional similarities of SL-RNAs are unlikely to have evolved repeatedly many times. Hence, we favor the scenario of an early evolutionary origin for the SLTS and multiple losses of SL-RNAs in various eukaryotic lineages.
Keywords: Sm-binding site; Intron; Phylogeny; Spliceosome; Trans-Splicing; Eukaryota; RNA secondary structure; RNA Precursors; molekulární evoluce; Evolution, Molecular; RNA, Spliced Leader; SL-RNA; trans-splicing; RNA se sestřihovou vedoucí sekvencí; fylogeneze; prekurzory RNA